Humanitarian Shelter Guidelines: Indonesian Version - Karsa, Keren Remaliah; Wardani, Laksmi Kusuma (Smart City, 2023)
No one can avoid disasters that could happen to anyone, anywhere, and anytime. Disasters might destoy people’s homes which are the primary need of human being. Therefore, people affected by disaster need new shelters to live in. Providing a shelter is not merely building a structure. However, shelter is a process of providing a better place for people especially those who are affected by disasters. Shelters and settlement assistance need to support a secure, dignified, and comfortable life. Ministry of Social Affairs Republic of Indonesia, coordinating with Indonesian Red Cross Society, published the Humanitarian Shelter Guidelines book in Indonesian version. This book contains informations regarding the basic understanding and paradigm of shelter, leading to determining the needs of shelters, guidelines on designing and planning shelter programs, implementing shelters and exit strategy, monitoring, and evaluating shelter and settlement assistance. All the informations completes the main purpose of providing better shelter for population affected by disaster. Therefore, this book is inclusively a pertinent reference to improve humanitarian shelter in Indonesia and worldwide.